Prevalence and associated factors of health facility delivery during COVID-19 in the Tamale Metropolis of Ghana: Analytical cross-sectional study - Obed Kwaku Duah Asumadu; Gilbert Abotisem Abiiro; Joyce Aputere Ndago; David Abatanie Kanligi; Martin Nyaaba Adokiya (PLoS ONE, 2026)
Introduction Globally, the COVID-19 pandemic significantly impacted the provision of maternal health services, especially facility-based delivery. However, there is little evidence on the proportion of women who delivered at the health facility in various locations and the factors that influenced women’s decision-making in choosing a place of delivery during and amid the COVID-19 restrictions. Therefore, this study assessed the prevalence and factors associated with health facility delivery during the COVID-19 pandemic in the Tamale Metropolis of Ghana. Methods An analytical cross-sectional study design was conducted. A multistage sampling technique was used in selecting the study communities. At the individual level, random sampling technique was applied, and 461 women were recruited from 21 st February 2021–21 st March 2021. Using a questionnaire, a face-to-face approach was used to conduct the interviews. The questionnaire included questions on socio-demographic characteristics, place of childbirth and factors that led to the choice of delivery place. Using Statistical Package for Social Sciences version 25, descriptive and binary logistic regression analysis were conducted. Results The results revealed that 64.0% of the women delivered in health facilities during the pandemic. Health facility delivery was more likely to occur among women with higher educational status (AOR: 5.2; 95% CI: 1.40–19.40), married women (AOR:6.3; 95% C.I:1.10–35.80), active National Health Insurance Scheme holders during delivery (AOR: 13.8; 95% C.I: 4.60–41.90), women who received education on birth preparedness and complication readiness (AOR: 7.6; 95% C.I:3.30–17.50) and women with underlying conditions before pregnancy (AOR:3.3; 95% C.I:1.20–9.20). There were reduced odds of health facility delivery among women with a history of home delivery (AOR:0.2; 95% C.I:0.10–0.50), when the mother-in-law decides on the place of delivery (AOR:0.1; 95% C.I:0.03–0.50), longer distance to the place of delivery (AOR:0.3; 95% C.I:0.01–1.00) and when women perceived COVID-19 as a barrier to facility delivery (AOR:0.1; 95% C.I:0.03–0.20). Conclusion Our findings show that health facility delivery declined during COVID-19. Factors that affected health facility delivery were educational status, marriage, having an active National Health Insurance Scheme, education on birth preparedness and complication readiness, underlying conditions before pregnancy, history of home delivery, mother-in-law decision on place of delivery, distance to place of delivery and perceiving COVID-19 as a barrier to facility delivery. These contributed to low facility delivery. Thus, maternal health services need to be brought to the doorsteps of communities, including proper implementation of the Focused Antenatal Care and community-based pregnancy school programmes, especially during future pandemics.